Postprandial In vitro Protease-Specific Activity of Nile Tilapia (Oreochromis niloticus L.) Digestive Organs - Anukoolprasert, Thatsanee; Srinuansom, Khajornkiat; Rukdontri, Thanasorn; Nonkhukhetkhong, Sataphon; Petkam, Rakpong (Pakistan Journal of Nutrition, 2019)
Background and Objective: Protease-specific activity varies postprandially. This study aimed to identify the optimum time after feeding Nile tilapia (Oreochromis niloticus L.) to collect digestive organ samples (stomach, proximal intestine, distal intestine and liver) to obtain maximum protease-specific activity values. Materials and Methods: One hundred Nile tilapia (average weight 55.19±1.78 g/fish) were acclimatized and fed two times per day for 14 days. At the beginning of the experiment, 6 fish were randomly taken from the tank before feeding (0 h) and then 6 fish were also randomly taken after feeding at 1, 3, 6, 12, 18, 24, 36 and 48 h for digestive organ collection. Homogenized organ pH was measured and extracted for a protease-specific activity assay using azocasein as a substrate. Results: The pH values of all organs differed (p